Rancangan Model Bisnis Pudidud (Puding Endud) Berbasis BMC - Prayitno, Rizqi Apriliani; Zahra, Cut; Najwa, Chika Naili Ilmatun; Ramadhani, Levina; Azhara, Dhea Fahmi; Ardiastati, Arfika; Ramadhani, Artika; Setiawati, Indah (Universitas Galuh, 2026)
Pudding is a popular dessert among various age groups.